Peer groups, social support, and well-being: Evidence from a large online maternity community - Lingqing Jiang; Zhen Zhu (University of Essex, Institute for Social and Economic Research (ISER), 2021)
Increasing attention is being paid to social determinants of health. We study how quasi-randomly assigned peer groups affect social support among over 24,000 pregnant women, and how social support in these peer groups relates to mothers' well-being both during and after pregnancy as well as birth outcomes. We find that while having more peer groups reduces observable social support in terms of information exchange, it does not seem to undermine perceived social support. Higher perceived social support from online peer groups is positively associated with both prenatal and postnatal mental health of the mothers as well as newborns' birth weight.
Keywords: I10; I31; J13; C36; 330; Social support; Peer groups; Mental health; IV; Survey